Toxic trace element contents in gluten-free cereal bars marketed in Argentina - Hidalgo, Melisa Jazmin (2015)
Celiac disease is a food intolerance triggered by the ingestion of gluten-containing cereals; the only therapy is a strict gluten-free diet for life. In recent years, gluten-free cereal bars has achieved considerable attention as an interesting alternative food considering its several advantages, such as functional properties, nutritional contents, variety of presentations and flavors. The aim of this study was to determine the contents of three toxic trace elements (arsenic, cadmium and lead) in commercial gluten-free cereal bars marketed in Argentina by ICP-MS and assess the dietary intake of the three toxic elements compared with reference values. The results obtained indicated that the highest total concentration of arsenic is provided by the gluten-free cereal bars with green apple pomace (28.2 μg/kg) and the levels of cadmium were lower than 10 μg/kg or even below MDL in all samples. The lead contents in all bars with honey samples were exceptionally higher than in the other samples (levels greater than 130 μg/kg). The intake of available gluten-free cereal bars are generally safe for consumers, but particular attention should be paid to monitor the content of arsenic and lead gluten-free cereal bars to ensure the quality of the product. Further studies are necessary to achieve an exact risk evaluation, concerning the bioavailability of trace elements in gluten-free food sources.